Associations between refractive error components and higher-order aberrations in simple myopia and compound myopic astigmatism - Mohaghegh, Sahar; Bamdad, Shahram; Kangari, Haleh; Rahmani, Saeed (Frontiers in Ophthalmology, 2025)
AimTo investigate associations between refractive error components and higher-order aberrations (HOAs) in adult myopic subjects.MethodsA total of 1370 myopia right eyes, aged 18-40, were included in a cross-sectional study. Subjective cycloplegic refractions and distance aberrometry measured with a Shack-Hartmann device were analyzed. Zernike components of horizontal coma (Z31), vertical coma (Z3-1), oblique trefoil (Z33), vertical trefoil (Z3-3), spherical aberration, and total root-mean-square (RMS) wave-front error for 6 mm pupil were analyzed. Pearson’s correlations were calculated between sphero-cylindrical components and HOAs based on vector analysis for the astigmatism axis. Total subjects were divided into two subgroups: simple myopia (SMY, 648 eyes) and compound myopic astigmatism (CMA, 722 eyes). HOAs were compared between the two subgroups.ResultsTotal RMS wave-front error correlates with spherical equivalent myopia (r = -0.1, P<0.05) and J45 (r = 0.1, P<0.001). J0 correlates positively with vertical coma (Z3-1) (r = 0.1 p <0.001) and negatively with oblique trefoil (Z33) and vertical trefoil (Z3-3), (r = -0.1, p < 0.001; r = -0.1, P < 0.05). The total RMS wavefront-error was larger in the CMA (|0.37| ± 0.18 µm) compared to the SMY (|0.34| ± 0.16 µm, P <0.001). The mean values of vertical coma (Z3-1), vertical trefoil (Z3-3), and oblique trefoil (Z33) differed between the two subgroups.ConclusionTotal RMS wave-front error increases with increasing myopia and astigmatism. Increasing myopia power does not show a systematic correlation with HOAs components. A weak systematic correlation is suggested between astigmatism direction and third-order aberrations.